The Effectiveness Of Health Education Through Instagram In Increasing Knowledge About Early Marriage - Syaharani, Erica Putri; Margono; Muslihatun, Wafi Nur (Jurnal Kesehatan Ibu dan Anak, 2023)
Early marriage is a reproductive health problem that risk adolescents whose increased significantly during this pandemic. Seeing the various impacts, promotive and preventive efforts need to be done the increasing of early marriage, one of which is health education. Health education can be done by utilizing technological developments, including social media Instagram. This study aims to determine the effectiveness of health education through Instagram in increasing adolescent knowledge about early marriage. This type of research is a pre-experimental with one group pre-test and post-test design. The sample was 80 students of class XI SMK Negeri 1 Saptosari with purposive sampling technique. The study was conducted in July 2022 and data collection was carried out online using a google form questionnaire and then data analysis using the wilcoxon test. The results showed that there was a difference in the average value of adolescent knowledge before (pre-test) and after (post-test) given health education about early marriage through Instagram, which was 61.14 before being given the intervention and increased to 82.95 after being given the intervention. With the Wilcoxon test results obtained a value of 0.000 (p <0.05), which means that health education through Instagram can increase adolescent knowledge about early marriage.